EVALUATION OF BIOLOGICAL ACTIVITY OF Crotalaria Juncea EXTRACTS THROUGH A Drosophila melanogaster MODEL - PEÑALOZA, Giann C.; PELÁEZ J., Carlos A. (Vitae, 2009)
The disproportionate growth of world population has led the search methods to control pests that permit a rational and sustained production of food, which additionally ensure the conservation of ecosystems. The activity of extracts with different polarity obtained from C. juncea was evaluated using the biological model of Drosophila melanogaster. This model allows the identification and purification of active fractions, and allows establishing that these extracts exert two different inhibitory activities over the life cycle of Drosophila melanogaster. The first activity showed the reduction in the number of adults compared with the control group. The second activity caused the inhibition of the larval estate then it resulted in diminution of the pupal number. The use of the biological assay and spectroscopy techniques as Nuclear Magnetic Resonance, allowed the establishment that the structure of active principle of Crotalaria juncea is in agreement with a pyrrolizidinic alkaloid of retronecic type well known as Junceine. The use of biological model as quantitative analytical tool, allows the establishment of correlation between dosage and response variables.